Pengakuan Agama Lokal sebagai Bentuk Pemenuhan Hak Warga Negara - Khaswara, Fajar; Vera, Susanti; Firdaus, Muhamad Yoga (Jurnal Riset Agama, 2021)
The adherents of indigenous religions are part of Indonesian society that has existed for a long time. But their rights are not fulfilled. In this study, the researcher aims to discuss the rights of adherents of indigenous religions. The research method used in this research is to use qualitative research with literature study. The results of this study contain a discussion of the history of the development of local religions, besides that this study also discusses local religious laws and rights in Indonesia, and this study also discusses the theory of minority influence applied to adherents of local religions. The conclusion of this study shows that the conflict between local and majority religions has existed since the Dutch era and this has an impact on local religious adherents who are marginalized in society. So that their rights are neglected as human beings and citizens.